Seküler iktisadi doktrinin eleştirisi çerçevesinde Ortadoğu-İslam toplumunda ekonomik entegrasyonun esasları - Erkekoğlu, Levent Coşkun (My University, 2015)
Bir toplumda sosyal adalet ve sosyal dayanışma amaçlandığı takdirde, toplumu oluşturan birimlerin tamamının maddi ve manevi ihtiyaçlarının karşılanması ve garanti altına alınması gereklidir. Toplumsal saadet ya da refah kavramından “sadece maddi mutluluk” algılandığı takdirde, manevi ihtiyaçların iktisadi sorunlara dâhil edilmediği anlaşılmaktadır. Bu durumda refah kavramı yalnızca “maddi zevklerin tatmini”nden ibarettir. Uluslararası iktisat, “yalnız kendisine hep daha fazlasını elde etmek için yaşayan insanların zevklerinin ve hazlarının toplamının artışının sağlanması”na odaklanmaktadır. Toplumsal refah seviyesindeki artışı “daha fazla tüketebilmek” olarak algılayan Geleneksel iktisadi zihniyet, Avrupa Aydınlanması esaslarına dayanmaktadır. Aydınlanma düşüncesine bağlı “kendi kendine işleyen piyasalar”, iktisadi ilişkilerde “insan doğasının” egoist davranış ilkesine dayandığı fikri savunur. “Seküler” esaslara dayanan ve egoist bireylerden oluşan “doğal düzen”de toplumun mutluluğu yerine önce bireysel mutluluk amaç edinildiği” için, “yalnızca merhametsiz, acımasız, dinsiz, gaddar ve maddi güç sahibi bireylerin mutluluğu” gaye edinilecektir ki bu bireylerin mutlulukları birbirleriyle çatışabilmektedir. Egoist ve çıkarcı bireylerden oluşan “doğal düzen” esasına dayalı bir toplumda dünyevi ve uhrevi saadeti temin etmek mümkün değildir. “Batı’lı zihniyete dayanan iktisadın egoist davranış motifi ve Allah inancı yerine insan aklını merkez yapan dünya görüşü”, Ortadoğu-İslâm toplumunun “Âhiret inancı gereği iktisadi yaşamının dayanışmacı anlayışı” ile çelişmektedir. Liberal sisteme dayalı iktisadın zihniyet temellerinde, düzenin Tanrısal olmadığı, sistemin merkezinin kişisel menfaat olduğu kabul edilmiştir. Hayatın iktisadi alanında amaç, en çok ve en özgür biçimde kişisel menfaat elde etmektir. Toplumsal yaşamın “doğal oyun düzeni” olduğu, her karar vericinin maksimum menfaat sağlamayı arzuladığı, egoist davranışın rekabet neticesini “doğal” olarak ortaya çıkardığı, egoizmin geliştirilmesinin faydalı olduğu ve iktisadi karar verici birimlere mutluluk getireceği inancı, İslami zihniyet esaslarına dayalı iktisat öğretisine aykırıdır. Geleneksel iktisadın “seküler zihniyet esasları” Darwinci zihniyete ve Pantheist inanca dayanması gerekçesiyle “seküler iktisadi bireyin”, “güçlünün zayıfı ezdiği bir mücadele olan iktisadi hayatta, dinsiz, gaddar ve acımasızca davranış göstererek, hiçbir engel tanımadan, her türlü kutsal değeri ezip geçerek, dünyevi menfaatine ulaşmayı kendisine bir amaç edinmesi” nin mümkün olmadığı ispat edilemez. “Her birimin bencilce ve rasyonelce davranarak yalnızca kendine maksimum çıkar sağlayan alternatifi tercih ettiğinde toplumun maksimum refaha ulaşacağı”na dair “ideal ve maksimum refah sağlayıcı doğal düzen” çelişkilidir. İktisadi aktörlerin başkalarının durumlarına kayıtsız kalarak yalnızca kendi çıkarları doğrultusunda hareket etmelerinin neticesi gayr-i ahlaki bir tavır sayılabilir. Bu zihniyet esasları pratikte, tabiat-perest ve materyalist felsefeye dayanmaktadır. Bu nedenlerle, Ortadoğu-İslâm toplumunun zihniyet esasları, Batı zihniyet esaslarına dayalı “seküler iktisadi anlayış”a uymamaktadır. İnsanın kâinattaki hedefi sadece kendi dünyevi mutluluğunu sağlamak olmadığı” için, “seküler iktisadi insan”ın nitelikleri, Kur’an hakikatlerine göre tarif edilen insanın en ehemmiyetli gayesinin manasına aykırı olduğu görülebilir. Bununla birlikte, İslami kuralların hükmündeki iktisadi düzende gerçekleşebilecek bir “toplumsal saadet ve refahın” başka hiçbir sistemde mümkün olmadığı anlaşılmaktadır. Yöntemine bakılmaksızın, iktisadi aktiviteler, “insanlığın gereği olan merhamet kavramına zıt düşen egoizm, hırs ve menfaatçilik esaslarına bağlı faiz müessesesine dayalı bir rejimde işlemektedir. Bir diğerine tepki olarak ortaya çıkan İktisat ekolleri, ahlaki kaideleri esas tutan ve adalet kavramını gerçekleştiren bir öğreti izlememişlerdir. İslâm’ın öğretisine aykırı olan “gücün hak doğurduğu” görüşüne bağlı tabiat-perest ve maddeci zihniyet, iktisadi birimlerin maddesel faydacı esasa bağlı olarak, “rasyonel davranışlar sonucunda toplamlı veya makro seviyede toplumsal oluşumlarını” açıklamaya yönelmiştir. Buna göre, toplumsal yaşamın iktisadi alanının en büyük mutluluğa, en çok hazza ve tatmine ve maddi çıkarlara erişmek amacında birbirilerinden mümkün olduğu kadar çok menfaat elde etmek isteyen iktisadi karar vericilerden meydana geldiği anlayışı hakimdir. Ancak İslâmi zihniyette, maddesel menfaat uğruna her şeyin feda edilmesi kabul edilebilir bir anlayış değildir. Semavi dinler insanlara huzur, düzen, dünyevi ve uhrevi hayatı için saadeti temin eden ilkeler, esaslar getirmiştir. Semavi dinlere göre, toplumda egoist ve merhametsiz davranışlarla her birimin kendi iktisadi başarısının peşinde olması aykırı bir görüştür. Bu demektir ki, “egoizm ve menfaatçilik, bilinç sahibi olanların bütünlüğüne, birliğine engeldir”. Buna göre, İslami yaşamda iktisadi davranışın ve motivasyonunun, İslami toplumun iktisadi saadetinin tanımının, İslami prensiplere uygun uluslararası iktisadi ilişkilerin hedefinin, uluslararası boyutta ekonomik bütünleşmenin temellerinin ve hedeflerinin “Seküler iktisad”ın doktrinine ve varsayımlarına göre açıklanması anlamsız ve çelişkili olacaktır. Ortadoğu-İslam Toplumunda iktisadi zihniyet kaidelerine bağlı bir sistem oluşturulması bir “gereklilik”tir. Bu “gereklilik” İslami kaidelere uygun bir ekonomik entegrasyon modeli ile somut bir çözüm haline gelebilir. “Sadece azami dünyevi zevk alma amacıyla iktisadi işlem”, Ortadoğu ve İslam Âlemi için umumun gayesini ve saadetini temin edemez. Orta Doğu-İslam dünyasının bir kaynaşma içerisinde olması, ekonomik bütünleşmeye doğru gitmesi için, Batılı zihniyet esaslarına talip olması çelişkilidir. Bütünleşmenin en önemli sebebi din ve ümmet anlayışıdır. Ortadoğu-İslam toplumu için “ekonomik entegrasyon” tercihi, entegrasyondaki ülkeler ve İslam Dünyası için “en iyi strateji” olacaktır. Bütünleşen ekonomilerin idare edilmesi gereği ve her ülkenin farklı olanaklara sahip olması gereği, aralarında muamelatta zulümler, aldatmalar olmaması için Şer’i hükümlerin ve Sünnet’in belirleyici olması zorunludur. Bundan dolayı, İslami ekonomik bütünleşmede en önemli esaslar faiz müessesesinin olmaması ve zekât müessesesinin olmasıdır. Toplumsal yaşamda dayanışma, sadaka, hıllet olmalıdır. Ortadoğu, İslâm, Entegrasyon, Seküler, İktisat, Doktrin.

If in a society, the aim is to establish the social justice and cooperation, it is inevitable to meet and see to the material and spiritual needs of each and every component that the society is composed of. If the perception from the social felicity or prosperity is ‘only materialistic happiness’, then it means the spiritual needs are not accounted into economical propositions. In this case, conception of prosperity consists of only satisfying the materialistic pleasure. International Economics focuses only on “increasing the enjoyments and pleasure of people who lead a life to gain more for themselves”. Conventional Economics’ mindset, that perceives the achievement of social prosperity as ‘being able to consume more and more’, is based upon the fundamentals of the European Enlightenment. Self-operating markets based upon the argument of the European Enlightenment sustain the idea that ‘Human Nature’ bears on the principle of egoism in economic relations. Since in the ‘Natural Order’ relying on “secular” basics and consisting of egoistic individuals, it is the priority to aim the individual happiness rather than the social happiness, ‘only the happiness of merciless, ruthless, irreligious, cruel and economically powerful individuals will be the real objective even so the happiness of these individuals are intersected at certain levels. It is impossible to establish the worldly and otherwordly felicity in a society that is based upon the “Natural Order” formed by egoistic and sordid individuals. Egoist behaviour model of the Economics that bears on the Western ideology and its worldview that puts human mind as a focal point in the place of the God faith is in deep conflict with the Middle East Islamic Society’s cooperative economics understanding due to its strong perception of hereafter. The mental foundations of Economics bearing on Liberal system refer to the centre of Natural Order as personal interest, not godlike. The main purpose of Economics in life is to gain freely the limitless personal interest and profit. It is against the mental principals of Islam to accept that; the Social life is a ‘natural game formation’, each individual is liable to desire the limitless interest, growing the egoism is a beneficial factor and all these bring happiness to individuals that make economic decisions. Since ‘secular mental principals’ of Conventional Economics refers to Darwinist and Pantheist essentials, it is unprovable that for a ‘secular economic individual’ in such Economical Environment, where the rich overwhelm the poor, it is not actually possible to to establish the worldly and otherwordly felicity in a society that is based upon the “Natural Order” formed by egoistic and sordid individuals. Egoist behaviour model of the Economics that bears on the Western ideology and its worldview that puts human mind as a focal point in the place of the God faith is in deep conflict with the Middle East Islamic Society’s cooperative economics understanding due to its strong perception of hereafter. The mental foundations of Economics bearing on Liberal system refer to the centre of Natural Order as personal interest, not godlike. The main purpose of Economics in life is to gain freely the limitless personal interest and profit. It is against the mental principals of Islam to accept that; the Social life is a ‘natural game formation’, each individual is liable to desire the limitless interest, growing the egoism is a beneficial factor and all these bring happiness to individuals that make economic decisions. Since ‘secular mental principals’ of Conventional Economics refers to Darwinist and Pantheist essentials, it is unprovable that for a ‘secular economic individual’ in such Economical Environment, where the rich overwhelm the poor, it is not actually possible to achieve the worldly interests by disregarding each spiritual value irreligiously, ruthlessly and cruelly. It is paradoxical to suggest that “the ideal Natural Formation (Natural Order) with circumstantial prosperity of the Society” is possible to be achieved if each individual selfishly and rationally choose the alternative lining on own pocket. It can be considered an unethical conduct for economic players to act only in pursuance of their own interests in ignorance of others. In practice, this approach is based on the naturalistic (worldly minded) and materialistic philosophy. Accordingly, the mindset of the Middle East-Islamic society does not match the “secular economic understanding” that is based on the Western mindset. Since the objective of the humankind in universe is not merely to secure his (secular) wordly prosperity, the attributes of “secular economic man” can be said to be contrary to the meaning of the most important objective of the humankind that is defined according to Qur’anic truth. However it turns out that ‘social prosperity and welfare’ that can be achieved in an economic order dominated by Islamic rules, is not possible in any other system. Regardless of the method, economic activities are carried out in an interest-based regime that is based on egoism, greed, and utilitarianism which is contrary to humane mercy.Appearing as a reaction to others, economic schools have not followed any discipline that is based on ethical rules, and that realizes the concept of justice. The naturalistic and materialistic mind, which depends on the idea that “force (power) brings right” in breach of Islamic discipline, has tended to explain “social formations at the aggregate or macro level as a result of rational behaviors.” Accordingly, the understanding is dominant that the economic area of social life comprises economic decision-makers who want to get the utmost benefit from each other in order to attain the highest pleasure, satisfaction, and material benefits. However the Islamic mindset does not accept to sacrifice everything for the sake of material benefits. Monotheistic religions have provided humankind with such principles that offer peace, order, and prosperity for his wordly and otherwordly lives. According to monotheistic religions, it is an anomalous opinion that each unit seeks for his own economic success by means of egoistic and merciless conducts in society. This means that egoism and utilitarianism is an obstacle against the integrity and unity of conscious creatures. Accordingly, it shall be nonsense and contradictory to explain the economic conduct and motivation favored in Islamic life, the definition of economic prosperity of the Islamic society, the objective of economic relationships that conform to Islamic principles, and the foundations and objectives of economic unity at international level based on the doctrine and assumptions of “Secular Economics”. It is a “necessity” to create a system based on the rules of an economic mindset in the Middle East and Islamic Society. This “necessity” can lead to a concrete solution through adaptation of an economic integration model that is based on Islamic rules. “The economic conduct that is only intended to attain the highest wordly pleasure” shall not secure the object and prosperity of public for the Middle East and Islamic Society. It is contradictory for the Middle East and Islamic Society to ask for the Western mindset to cohere into an economic unity. The most important cause of integrity is the religion and Ummah. The preference of “economic integration” for the Middle East and Islamic Society shall be “the best strategy” for the countries in integration as well as for the Islamic World. It is mandatory to apply Sharia law and Sunnah due to the requirement to administrate integrated economies, due to the fact that each country has different resources, and in order to prevent oppressions and deceptions among them. Accordingly, the most important principles of the Islamic economic integration is the lack of interest mechanism and the presence of zakat mechanism. The social life must incorporate solidarity, charity, and neighborliness. ddle East, Islam, Integration, Secular, Economics, Doctrine
Keywords: Dini Yönleri; Dinsel Yönler; Ekonomi; Ekonomi Politikası; İslam; Ortadoğu